2017
DOI: 10.3390/molecules22020283
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supply Affects Anthocyanin Content and Related Gene Expression in Berries of Vitis vinifera cv. Cabernet Sauvignon

Abstract: Anthocyanins are important compounds for red grape and red wine quality, and can be influenced by supply of nutrients such as nitrogen, phosphorus, potassium, zinc, and iron. The present work aims to gain a better understanding of the effect of iron supply on anthocyanins concentration in grape berries. To this end, own-rooted four-year-old Cabernet Sauvignon grapevines (Vitis vinifera) were fertigated every three days with 0, 23, 46, 92, and 184 μM iron (Fe) from ferric ethylenediamine di (o-hydroxyphenylacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…Our results are in agreement with those of Mohammadi et al [68] where anthocyanin concentration in peppermint increased by 11.5% with 0.5g L −1 Fe 2 O 3 treatment in comparison to the control treatment (0 g L −1 Fe 2 O 3 ). The non-linear dose response recorded in our experiment was in line with the findings of Shi et al [69], who found that total anthocyanin concentration of Cabernet Sauvignon grapes under Fe deficient and excess treatments (0, 23, 92 and 184 µM Fe) were lower than that of the 42 µM Fe treated grapes. The improvement of anthocyanin synthesis at 42 µM Fe has been associated to several mechanisms including the accumulation of sugar and the expression of several structural genes in the flavonoid pathway.…”
Section: Hydrophilic Antioxidants: Ascorbic Acid and Phenolics Profilesupporting
confidence: 93%
“…Our results are in agreement with those of Mohammadi et al [68] where anthocyanin concentration in peppermint increased by 11.5% with 0.5g L −1 Fe 2 O 3 treatment in comparison to the control treatment (0 g L −1 Fe 2 O 3 ). The non-linear dose response recorded in our experiment was in line with the findings of Shi et al [69], who found that total anthocyanin concentration of Cabernet Sauvignon grapes under Fe deficient and excess treatments (0, 23, 92 and 184 µM Fe) were lower than that of the 42 µM Fe treated grapes. The improvement of anthocyanin synthesis at 42 µM Fe has been associated to several mechanisms including the accumulation of sugar and the expression of several structural genes in the flavonoid pathway.…”
Section: Hydrophilic Antioxidants: Ascorbic Acid and Phenolics Profilesupporting
confidence: 93%
“…The roles of these genes in iron homeostasis and plant physiological functions are diverse. Iron supply can affect anthocyanin concentrations and the transcript abundance of genes in the phenylpropanoid pathway in Cabernet Sauvignon berry skins [76]. One of the DEGs, SIA1, is located in the chloroplast in Arabidopsis and appears to function in plastoglobule formation and iron homeostasis signaling in concert with ATH13 (also known as OSA1) [77].…”
Section: Transcript Abundance Of Iron Homeostasis Genesmentioning
confidence: 99%
“…and plant physiological functions are diverse. Iron supply can affect 17 anthocyanin concentrations and the transcript abundance of genes in the 18 phenylpropanoid pathway in Cabernet Sauvignon berry skins [76]. One of 19 the DEGs, SIA1, is located in the chloroplast in Arabidopsis and appears to 20 function in plastoglobule formation and iron homeostasis signaling in concert 21…”
Section: Simultaneouslymentioning
confidence: 99%